The Common but Differentiated Responsibilities Principle: An excuse for weak climate targets? - Blumenthal, Corinne (Université d'Ottawa | University of Ottawa, 2023)
The Common But Differentiated Responsibilities (CBDR) principle in global climate politics recognizes that all states have a common responsibility to mitigate the climate crisis, yet they have differing capabilities to respond to the crisis and different historical contributions to the state of the current environment. This paper seeks to understand the relevance of the CBDR principle in today’s global climate regime, namely considering the role played by high-emitting emerging countries such as China. Specifically, the paper asks: Has the CBDR principle allowed China to hide from climate action? Through an integrative literature review and a combination of discourse and historical analysis, I find that although the CBDR principle has helped China delay climate commitments such the phasing out of fossil fuels, China has not entirely hidden behind the principle to avoid ambitious climate action and has assumed a greater leadership role in the global climate regime in the last decade. The findings in this paper help situate the role of high-emitting emerging countries in global climate politics, as well as the importance of the CBDR principle today. Keywords: Common But Differentiated Responsibilities Principle, CBDR, Global Climate Regime, China, Equity